Fabrication of CuW electrode for producing micro-hold on Wc-Co using EDM process - Hourmand, Mehdi (2013)
Micro-machining is one of the fundamental technologies for manufacturing miniaturized parts and products with size of between 1 to 999 µm. A micro-mold cavity is required for the mass production of micro component using injection molding machine. Moreover, micro-holes are also required in a micro-die. Nowadays, WC and its composite (WC-Co) are the widely used material in the making of cutting tools, dies and other special tools and components. Therefore, machining of WC is an important activity in manufacturing. Micro-EDM is one of the most effective methods for machining WC. Unfortunately there is limited information available about fabricating micro-hole electrode made from CuW for electrical discharge machining. This includes information on suitable electrode material for electrical discharge machining of CuW, the processing method and suitable parameter for micro-EDM of CuW and WC-Co. In this research, PGM WHITE 3 is used as the dielectric fluid, Cu-W as the micro-electrode, WC-Co as the workpiece material and Sodik AG40L as the die-sinking machine selected for the project. Process parameters investigated are polarity and voltage while the effects investigated are time of machining, end wear and diameter of hole. An electrode with a diameter of 372.76 µm has been successfully fabricated using selected process. Results of the experiment show that Micro-electrode with negative polarity has lower end wear of tool than positive polarity. Negative polarity of micro-electrode is used for micro-EDM of hole and positive polarity of micro-electrode is used for facing of micro-electrode. Lowest end wear of electrode has been achieved at P of CuW (-), IP (0.4 A), ton (1 µs), Df (0.5), Sr (20 rpm), Eg (50). Lowest hole diameter has been achieved at P of CuW (+), IP (0.4 A), ton (1 µs), Df (0.5), Sr (20 rpm), Eg (70). The shortest time of machining is achieved at P of CuW (-), IP (0.4 A), ton (1 µs), Df (0.5), Sr (20 rpm) Eg (70) when investigating 50, 70 and 90V